Successful treatment of cutaneous polyarteritis nodosa with baricitinib - Shihui Zhou; Zhen Zhang; Zhirong Yao; Yifeng Guo (Journal of Dermatological Treatment)
The purpose of the article: Polyarteritis nodosa (PAN) is a rare systemic necrotizing vasculitis preferentially targeting medium-sized arteries. PAN has two clinical entities: systemic PAN (sPAN) and cutaneous PAN (cPAN). cPAN is a skin-limited vasculitis, while ulcerative cPAN often predicts a higher risk of recurrence and a worse prognosis. However, there is still little experience and no consensus on cPAN treatment. Janus kinase-signal transducer and activator of transcription (JAK-STAT) inhibition with baricitinib (JAK1/JAK2) inhibitor in patients with inflammatory skin diseases has demonstrated good therapeutic outcomes in several clinical studies. However, the use of baricitinib in patients with cPAN has not been reported to date.Materials and methods: We report the first case of cPAN successfully treated with baricitinib. The patient had previously undergone various treatments, including corticosteroids and immunosuppressants, but these were continually switched due to inadequate efficacy or significant side effects.Results: Following treatment with baricitinib, the patient’s ulcers healed, subcutaneous nodules resolved, and livedo reticularis alleviated, resulting in a marked improvement in quality of life. No severe adverse reactions were observed during the treatment period. Over 1 year of follow-up, there was no recurrence of the rash.Conclusions: Our results support the evidence that baricitinib is a promising therapy for cPAN.